PELATIHAN MEDIA PEMBELAJARAN BERBASIS GAME “EDUNOMIC ADVENTURE” UNTUK MAHASISWA FKIP UNIVERSITAS PALANGKA RAYA - Putra , Kharisma Nugraha; Eriawaty, Eriawaty; Rahman, Rahman; Hariatama, Fendy; Buji, Grace Evelina (Universitas Negeri Surabaya, 2025)
Digital technology plays a crucial role in the education system today. One tangible example of the integration of digital technology with education is the rise of educational games as interactive learning tools. The purpose of conducting a Community Service Program (PkM) in the form of training on game-based learning media is to assist students of the Faculty of Teacher Training and Education (FKIP) at Palangka Raya University in developing educational game-based learning media that can be implemented by students in developing technology-based learning media. The Community Service was held at the Red and White Building of Palangka Raya University. The training took place on Wednesday, November 15, 2023, attended by 38 participants who were students of the Economics Education Study Program, Faculty of Teacher Training and Education, Palangka Raya University. The participants of the training were interested in using game-based learning media as one of the methods that can be employed in the teaching and learning process. Furthermore, students were motivated to develop other learning media, especially by utilizing digital technology.